Enrollment Yield and Reasons for Screen Failure in a Large Prehospital Stroke Trial - Kim, Dae-Hyun (Stroke, 2015)
BACKGROUND AND PURPOSE: The enrollment yield and reasons for screen failure in prehospital stroke trials have not been well delineated. METHODS: The Field Administration of Stroke Therapy – Magnesium (FAST-MAG) trial identified patients for enrollment using a two stage screening process - paramedics in person followed by physician-investigators by cellphone. Outcomes of consecutive screening calls from paramedics to enrolling physician-investigators were prospectively recorded. RESULTS: From 2005 to 2012, 4,458 phone calls were made by paramedics to physician-investigators, an average of one call per vehicle every 135.7 days. A total of 1,700 (38.1%) calls resulted in enrollments. The rate of enrollment of stroke mimics was 3.9%. Among the 2,758 patients not enrolled, 3,140 reasons for screen failure were documented. The most common reasons for non-enrollment were: more than 2 hours from last known well (17.2%), having a prestroke condition causing disability (16.1%), and absence of a consent provider (9.5%). Novel barriers for phone informed consent specific to the prehospital setting were infrequent, but included: cellphone connection difficulties (3.2%), patient being hard of hearing (1.4%), insufficient time to complete consent (1.3%) or severely dysarthric (1.3%). CONCLUSIONS: In this large, multicenter prehospital trial, nearly 40% of every calls from the field to physician-investigators resulted in trial enrollments. The most common reasons for non-enrollment were out of window last known well time, prestroke confounding medical condition, and absence of a consent provider. CLINICAL TRIAL REGISTRATION—URL: http://www.clinicaltrials.gov. Unique identifier: NCT00059332. Barrier to completion of prehospital phone informed consent